Strokes: mimics and chameleons. Issue 1 (13th January 2013) - Fernandes, Peter M; Whiteley, William N; Hart, Simon R; Al-Shahi Salman, Rustam
Abstract : Diagnosing stroke is not always straightforward. Stroke mimics such as Todd's paresis or hemiplegic migraine account for between a fifth and a quarter of suspected strokes (depending on the setting in which they are assessed). Stroke chameleons can arise when the tempo of symptom onset is not apoplectic or if the loss of function is not clearly consistent with a deficit within an arterial territory. Thrombolysis and secondary prevention have much to offer patients with stroke chameleons, though those with stroke mimics may be harmed by these treatments and have more to gain from other therapies.